Antibiotic usage and auditing of antibiotic sensitivity pattern of culture positive neonatal septicemia in neonatal intensive care unit of a tertiary care hospital: a retrospective study - Nagesh, H. N.; Basavanna, P. L.; Savitha, M. R. (International Journal of Contemporary Pediatrics, 2017)
Background: Antibiotic resistance is an emerging problem in neonatal intensive care units (NICU) particularly in developing countries. The spectrum of organisms that cause neonatal sepsis changes from time to time and varies from region to region. Hence continuous surveillance for antibiotic susceptibility, rational use of antibiotics and the strategy of antibiotic cycling can provide some answers to it. the present study was undertaken to study the various antibiotics used and to analyze the antibiotic sensitivity and resistance pattern in NICU of tertiary care hospital. Methods: The clinical files of neonates admitted in the NICU of Cheluvamba Hospital, Mysore from April to September 2012 were revised. The diagnosis, antibiotics used, culture and sensitivity were collected. The data were analyzed using SPSS version 17.0. Results: A total of 185 blood culture positive reports were analyzed. Most commonly used empirical antibiotic was amikacin (96.2%) followed by cefotaxime (57.3%) and piperacillin-tazobactam (28.1%). Commonly used combination antibiotics were amikacin and cefotaxime (58.6%), followed by amikacin and piperacillin-tazobactam (28.7%). Rarely vancomycin (3.8%) or meropenem (1.7%) were used as first-line antibiotics in severe sepsis. Piperacillin-tazobactam (21.6%) followed by vancomycin (19.5%) were commonly used as second line drugs. Organisms showed maximum resistance against penicillins (91.7%), ceftazidime (96.9%), cefotaxime (85.3%), cefoxitin (75.6%), ceftriaxone (72.4%) and amikacin (55%) and maximum sensitivity to vancomycin (100%), linezolid (100%), imipenem (92.3%), netilmicin (60%) and piperacillin-tazobactum (52.4%). Conclusions: (1) There is an emerging resistance against cephalosporins (including 3rd generation) and amikacin, (2) vancomycin, linezolid, imipenem are showing maximum sensitivity and hence should be kept in reserve for resistant cases.